MENINGKATKAN KEMAMPUAN MEMBACA RAMBU-RAMBU DI SEKITAR MELALUI PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING PADA SISWA KELAS II SEKOLAH DASAR : Penilaian Tindakan Kelas - Riyanti, Nunik; Nurhadi, Nurhadi; Trisnawati, Nurmasari; Indrawati, Delia; Wahyu Listiani, Wiwik; Nur Cahyanti, Novita; Fauziah, Nining (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning with the application of role playing aims to make students more meaningful to the rules in public places, especially reading the signs around them, and is taught in grade II of Elementary Schools in Surabaya. The research conducted using classroom action research techniques carried out in two stages, namely pre-cycle, cycle one and cycle two. The subjects in the research conducted were grade II students at Elementary Schools in Surabaya, with a total of 28 students. Data collection techniques were through Observation and written tests on students. So that the overall data that has been obtained is then analyzed by: 1) conducting research on data review, 2) calculating the results of the data obtained, 3) presenting the results of the data, and 4) concluding the results of the research. The results obtained after the application of role playing were that there were 14 out of 28 students who were able to complete their learning on the test in the pre-cycle. Then in cycle one there were 24 out of 28 students who were able to complete their learning, the last in the second cycle with the improvement of the role playing approach, there were 26 out of 28 students who were able to complete the learning. So that the ability of students in learning rules in public places from cycle one to cycle two experienced a good increase, with an average understanding of 76,8 to 8,6.